Diatom distributions in northern North Pacific surface sediments and their relationship to modern environmental variables. - Ren, Jian; Gersonde, Rainer; Esper, Oliver; Sancetta, Constance A (PANGAEA, 2014)
In order to map the modern distribution of diatoms and to establish a reliable reference data set for paleoenvironmental reconstruction in the northern North Pacific, a new data set including the relative abundance of diatom species preserved in a total of 422 surface sediments was generated, which covers a broad range of environmental variables characteristic of the subarctic North Pacific, the Sea of Okhotsk and the Bering Sea between 30° and 70°N. The biogeographic distribution patterns as well as the preferences in sea surface temperature of 38 diatom species and species groups are documented. A Q-mode factor analysis yields a three-factor model representing assemblages associated with the Arctic, Subarctic and Subtropical water mass, indicating a close relationship between the diatom composition and the sea surface temperatures. The relative abundance pattern of 38 diatom species and species groups was statistically compared with nine environmental variables, i.e. the summer sea surface temperature and salinity, annual surface nutrient concentration (nitrate, phosphate, silicate), summer and winter mixed layer depth and summer and winter sea ice concentrations. Canonical Correspondence Analysis (CCA) indicates 32 species and species groups have strong correspondence with the pattern of summer sea surface temperature. In addition, the total diatom flux data compiled from ten sediment traps reveal that the seasonal signals preserved in the surface sediments are mostly from spring through autumn. This close relationship between diatom composition and the summer sea surface temperature will be useful in deriving a transfer function in the subarctic North Pacific for the quantitative paleoceanographic and paleoenvironmental studies. The relative abundance of the sea-ice indicator diatoms Fragilariopsis cylindrus and F. oceanica of >20% in the diatom composition is used to represent the winter sea ice edge in the Bering Sea. The northern boundary of the distribution of F. doliolus in the open ocean is suggested to be an indicator of the Subarctic Front, while the abundance of Chaetoceros resting spores may indicate iron input from nearby continents and shelves and induced productivity events in the study area.
Diatom abundance in surface sediments of the northern North Pacific
Keywords: 2172; 2176; 2177; 2182; 2185; 2217; 2219; 2220; 2223; 2227; 2228; 2252; 2254; 2256; 2259; 2262; 2266; Academy of Science Rise; Achnanthes lanceolata; Achnanthes minutissima; Achnanthes spp.; Actinocyclus cf. octonarius; Actinocyclus curvatulus; Actinocyclus ochotensis; Actinocyclus octonarius; Actinocyclus oculatus; Actinocyclus sp.; Actinocyclus spp.; Actinoptychus senarius; Actinoptychus splendens; Actinoptychus vulgaris; Akademik A Nesmeyanov; Akademik M.A. Lavrentyev; Alveus marinus; Amphora spp.; Asteromphalus brookei; Asteromphalus hyalinus; Asteromphalus marylandicus; Asteromphalus robustus; Aulacoseira granulata; Aulacoseira spp.; AWI_Paleo; Azpeitia nodulifer; Azpeitia tabularis; Bacillaria paxillifer; Bacterosira bathyomphala; BB311-017; BB311-026; BB311-039; Bering Sea; Chaetoceros, resting spores; Chaetoceros atlanticus; Chaetoceros diadema, resting spores; Chaetoceros furcellatus; Cocconeis californica; Cocconeis costata; Cocconeis pellucida; Cocconeis placentula; Cocconeis scutellum; Cocconeis spp.; Coscinodiscus marginatus; Coscinodiscus oculus-iridis; Coscinodiscus radiatus; Counting, diatoms; CTD/Rosette; CTD-RO; Cyclotella litoralis; Cyclotella ocellata; Cyclotella spp.; Cyclotella striata; Cymbella spp.; Delphineis kippae; Delphineis spp.; Delphineis surirella; Denticula spp.; DEPTH, sediment/rock; Derugin Basin; Detonula confervacea, resting spores; Diatoma spp.; Diploneis bombus; Diploneis chersonensis; Diploneis litoralis; Diploneis smithii; Diploneis spp.; Eastern continental slope of Sakhalin; Eastern slope of Kurile Basin; Entomoneis spp.; Eunotia curtagrunowii; Eunotia monodon; Eunotia spp.; Fallacia spp.; Fossula arctica; Fragilaria capucina; Fragilaria construens; Fragilaria martyi; Fragilaria spp.; Fragilariopsis atlantica; Fragilariopsis cf. oceanica; Fragilariopsis cylindrus; Fragilariopsis doliolus